Audit of observation ward supporting emergency room at tertiary care hospital: Kathmandu, Nepal - Shakya, Yogendra Man (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: Tribhuvan University Teaching Hospital is a tertiary care hospital of Nepal. In an average, 118 cases visit TUTH emergency per day. After initial management in Emergency, patients are either admitted in specialty departments or are observed in observation ward under Department of General Practice. Method: It was audit report carried out among the patients admitted to observational ward of TUTH. It included data of one month. Result: Total of 205 patients were admitted to observation ward, 16 (7.8%) were later on transferred in various other wards of hospital and 189 (92%)patients were admitted in the observation ward. The common admitting diagnosis was seen to be Dengue fever82(40%), followed by COPD 20(9.7%). Conclusion: For those patients presenting in emergency room, observation wards is better alternative for continuing medical care after getting emergency care.